Physico-Chemical and Organoleptic Characteristics of Cookies Made from Snake Fruit Cultivar Pondoh Flour (Sallaca edulis Reinw.) and Palm Stem Starch (Arenga pinnata Merr.) - Kumalasari, Ika Dyah; Pradnya Paramitha, Dyah Ayu (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2024)
Snake fruit is a food that has a fairly high fiber content and also has vitamin C content. Palm stem starch has starch content so it is used to soften the texture of cookies and also has a high fiber content. The use of snake fruit and palm stem starch aims to produce a cookie formulation that is healthier than commercial cookies with high fiber and vitamin C content. The purpose of this study was to determine the physico-chemical and organoleptic properties of cookies made from snake fruit cultivar pondoh flour and palm stem starch. This study used a completely randomized design (CRD) consisting of 5 formulations with 3 replications, namely the ratio of palm stem starch flour and snake fruit cultivar pondoh flour 100%:0% (F1), 75%:25% (F2), 50%:50% (F3), 25%:75% (F4) and 0%:100% (F5). Data were analyzed using One-Way ANOVA and Duncan's further test with 5% significance level. The experiment was conducted by testing physico-chemical and organoleptic properties on 30 untrained panelists. The results showed that making cookies made from snake fruit cultivar pondoh flour and palm stem starch flour had a significant effect on the physico-chemical and organoleptic properties of cookies. The results obtained are water content 4,96%-6,77%; ash content 1,97%-2,88%; fat content 11,78%-14,37%, protein content 6,34%-8,48%; carbohydrate content 57,05%-63,66%; crude fiber content 9,45%-12,25%; vitamin C content 1,00 mg- 2,87 mg; hardness 154,55 N-523,14 N; color L* 29,39-66,05; color a* 2,27-7,84; color b* 10,92-33,86; and organoleptic test color 1,80-4,43; aroma 2,57-3,92, texture 1,87-4,43, taste 1,97-4,23, overall 2,20-4,30.